The future is Asian global order in the twenty-first century - Khanna, Parag (London Weidenfeld & Nicolson, 2019)
Five billion people, two-thirds of the world's mega-cities, one-third of the global economy, two-thirds of global economic growth, 30 of the Fortune 100, six of the 10 largest banks, eight of the 10 largest armies, five nuclear powers, massive technological innovation, the newest crop of top-ranked universities. Asia is also the world's most ethnically, linguistically and culturally diverse region of the planet, eluding any remotely meaningful generalisation beyond the geographic label itself. Even for Asians, Asia is dizzying to navigate.
Includes index
Keywords: Geopolitics